2012
DOI: 10.2478/v10078-012-0081-x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Yo-Yo Tests, Anaerobic Performance and Aerobic Performance in Young Soccer Players

Abstract: The purposes of this study were to determine the relationship between performance in the Yo-Yo intermittent recovery test level 1 (YIRT1), the Yo-Yo intermittent recovery test level 2 (YIRT2) and the Yo-Yo endurance test (continuous) (YET) with maximal oxygen uptake (VO2max) and Wingate anaerobic performance (WaNT) test results in young soccer players (age 15.00 ± 0.0 years, body height 176.3 ± 4.2 cm and body mass 68.1 ± 3.6 kg). An ergospirometry device was used during the treadmill test (TRT) to determine V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 20 publications
(42 reference statements)
2
30
0
6
Order By: Relevance
“…This result is consistent with the findings reported in many research papers on the same subject [6, 19, 21, 34, 35, 39]. The relationships between V.O 2 max and the FI for repeated sprints found in this and the above studies seem to indicate that aerobic processes play a role in the recovery of energy substrates, which are necessary to exercise at high intensity.…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with the findings reported in many research papers on the same subject [6, 19, 21, 34, 35, 39]. The relationships between V.O 2 max and the FI for repeated sprints found in this and the above studies seem to indicate that aerobic processes play a role in the recovery of energy substrates, which are necessary to exercise at high intensity.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, Rampinini et al (2010), Ueda et al (2011), Karakoç et al (2012), and Bangsbo et al (2008 found a low or moderate degree of association between V O2max and the final distance. In this study, a positive correlation in the U20 group was found between the variables that reflect the internal load or cardiorespiratory fitness (V Opeak and V O2 at VT) and those that reflect the external load or the performance in the test (Dmax and Smax), but not in the O20 group.…”
Section: Peak Oxygen Uptake Ventilatory Threshold and Performance Inmentioning
confidence: 87%
“…For example, Krustrup et al (2003), Thomas et al (2006) and Rampinini et al (2010) found a strong correlation between YYIR1 and VO2max performance; Castagna et al (2006) found no correlation and Karakoç et al (2012) found a moderate correlation. As for YYIR2, Rampinini et al (2010) found a weak correlation, while Krustrup et al (2006) and Karakoç et al (2012) found a moderate correlation.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations